SUBSTITUSI DADIH SEBAGAI PENGGANTI YOGHURT DALAM PEMBUATAN YOGHURT SORBET - Hayati, Miftahul; Nuryanto, Heri (JURNAL MANAJEMEN KULINER, 2024)
For the people of West Sumatra, especially Bukit Tinggi, curd is a very popular food because curd is often found in the area. Apart from that, Dadih is a fermented milk product made from buffalo milk from West Sumatra. Yoghurt is fermented milk using a mixed culture of microorganisms such as lactobacillus bulgaricus and Streptococcus thermophilus, resulting in a pudding-like consistency. Yoghurt is a dairy product that uses two or more bacterial cultures. Judging from its nutritional content, yogurt is very rich in calcium and iron, which are substances that are good for bone loss. Dadih is a typical Minang Kabau food made from fermented buffalo milk shaped like yoghurt using bamboo as a wrapper. Yoghurt is a highly nutritious food that helps improve health. The bacteria in yoghurt also coat and acidify the intestinal walls, preventing disease-causing microbes from multiplying in yoghurt. This study required 10 somewhat trained panelists and 20 untrained panelists. The data collection techniques used in this research are hedonic tests and hedonic quality tests using questionnaires. The research results showed that curd sorbet with a ratio of curd and yoghurt had significant differences in the aspects of color, aroma, taste and texture. People were more interested in the color, aroma, taste and texture of treatment sample 3 (50%) because it had a bright white color, quite sour aroma, a very sour taste and a soft texture.